1972
DOI: 10.1111/j.1471-4159.1972.tb01309.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF MODERATE AND MARKED HYPERCAPNIA UPON THE ENERGY STATE AND UPON THE CYTOPLASMIC NADH/NAD+ RATIO OF THE RAT BRAIN

Abstract: The energy state of brain tissue was evaluated from the tissue concentrations of ATP, ADP and AMP and the cytoplasmic NADH/NAD + ratio from the tissue, CSF and blood concentrations of lactate and pyruvate, and from the intracellular pH', in rats exposed to carbon dioxide concentrations of 6 4 0 per cent. The hypercapnia had no significant effect on the energy state of the tissue. Hypercapnia of increasing severity gave rise to a progressive decrease in the pyruvate concentration ; the lactate concentration fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

1973
1973
1991
1991

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(55 citation statements)
references
References 18 publications
3
51
0
1
Order By: Relevance
“…Since no ac tivation of PDHC with DCA was noted at 15 min of recirculation, the decreased levels of pyruvate could not be explained by a change in PDHC activ ity. A decrease in intracellular pH could account for the observed increase in lactate/pyruvate ratio, as was also found in hypercapnia (Folbergrova et al, 1972), and which is also indicated by the decreased PCr levels in the DCA + glucose-treated animals. However, the observed changes in intermediary metabolism apparently did not affect the PDHC ac tivity.…”
Section: Discussionmentioning
confidence: 62%
“…Since no ac tivation of PDHC with DCA was noted at 15 min of recirculation, the decreased levels of pyruvate could not be explained by a change in PDHC activ ity. A decrease in intracellular pH could account for the observed increase in lactate/pyruvate ratio, as was also found in hypercapnia (Folbergrova et al, 1972), and which is also indicated by the decreased PCr levels in the DCA + glucose-treated animals. However, the observed changes in intermediary metabolism apparently did not affect the PDHC ac tivity.…”
Section: Discussionmentioning
confidence: 62%
“…Samples of the parietal cortex and the hippocampus were dissected out from the brain at -22°C and assayed for metabolites and FFAs according to previously re ported methods (Folbergrova et al, 1972;Rehncrona et aI., 1982).…”
Section: Determination Of Labile Energy Metabolites and Ff Asmentioning
confidence: 99%
“…Samples were dissected and extracted with HCI-methano1 at -22°C and subsequently with perchloric acid at O°C, as previously described (26). Metabolites were measured with enzymatic fluorimetric techniques of Lowry and Passonneau (27). The adenylate energy charge (E.C.…”
Section: Materials a N D Methodsmentioning
confidence: 99%